Chemical composition of essential oils from the leaves of Mosiera bullata (Britton & P.Wilson), an unexplored Cuban endemic species. Issue 2 (4th March 2022) - Goya-Jorge, Elizabeth; Fernández Expósito, Osmary; Herrero-Martínez, José Manuel; Simó-Alfonso, Ernesto F.; Castañeda-Noa, Idelfonso; Jorge Rodríguez, María Elisa
ABSTRACT: Mosiera Small is a genus of Myrtaceae family with about forty species identified, including the Cuban endemic plant Mosiera bullata (Britton & P.Wilson) Bisse subsp. bullata. Mosiera species have been little investigated, and this is the first study analysing the composition of Mosiera bullata . Fresh leaf samples of M. bullata were collected from different locations near Santa Clara city, Cuba, and their essential oil was extracted. Using GC/MS, nineteen components (89.68% of the oil) were identified. The major compounds were found to be 1, 8-cineole and eugenol, and a GC/FID method was analytically validated for their quantification. Chromatograms (GC/FID) of the sixteen samples studied were proposed as a fingerprint of the volatile composition of M. bullata leaves. Chemometric methods assured the reliability of the chromatographic fingerprinting. Therefore, in the present work is suggested, for the first time, a reliable and consistent chemical profile of M. bullata essential oil.